Efek Nefroprotektif Ekstrak Daun Sirsak (Annona muricata L.) pada Mencit Model yang Diinduksi Parasetamol - Nur Hidayah; . Suyatmi; Ratih Puspita Febrinasari (Nexus Biomedika, 2014)
Background: Soursop Leaf (Annona muricata L.) contains active compounds that have antioxidant effects consisting of flavonoid, alkaloid, tannin, triterpenoid and steroid. The aim of this research is to know the protective effect of Soursop Leaf Extract on the renal histological damage of mice induced by paracetamol Methods: This study was experimental research with the post test only controlled group design. Samples were 30 male Swiss webster mice, 2-3 months old and 20 g of body weight. Samples were divided randomly into 5 groups, each group consisted of 6 mice. The normal group (KN) and negative control group (KKn) were given distilled water for 14 days. KP1, KP2, and KP3 were given soursop leaf extract in dose 5.6 mg, 11.2 mg, and 22.4 mg per g of body weight of mice, respectively, for 14 days. Paracetamol in dose 5.07 g per 20 g body weight of mice were given to KKn, KP1, KP2, and KP3 on the 12th ,13th ,14th days. On the 15th day mice were sacrificed and then renal organ were taken for histological preparation and stained with HE. Renal histological features were assessed based on quantifying of necrotic cells (pyknosis, karyorrhexis, karyolysis) of 50 epithelial cells from proximal tubule of right and left renal organ. Data were analyzed using One-Way ANOVA test and continued with Post Hoc (LSD) test. Results: The means of necrotic cells for KN, KKn, KP1, KP2, and KP3 were 8.17, 38.58, 26.92, 21.08 and 11.67, respectively. The One-Way ANOVA test showed a significant difference of renal damage score in five groups with p = 0.000. The Post Hoc LSD test also showed significant difference among five groups, p = 0.000. Conclusion: Soursop leaf extract can prevent the histological damage of renal cells on mice induced by paracetamol. Keywords: Soursop leaf extract, paracetamol, renal histological damage